Maize hybrids response to high plant density in the Guinea savannah of Nigeria - Kamara, A.; Menkir, A.; Abubakar, A.W.; Tofa, A.; Ademulegun, T.; Omoigui, L.; Kamai, N. (Informa UK Limited, 2021)
Several maize (Zea mays L.) hybrids have been developed and commercialized in the Nigeria savannas, but limited informationis available on how they perform at plant densities higher than the recommended density of 53,333 plants ha-1. Therefore, field trials were conducted in northern Nigeria in 2015 and 2016 at two locations with contrasting rainfall amount to evaluate the performance of selected maize hybrids at plant densities of 53,333 and 88,888 plants ha-1. All maize hybrids had higher grain yields, total dry matter, ears m-2, and number of grains m-2 at 88,888 than at 53,333 plants ha-1 at both locations. The magnitude ofincreases in yield when plant density was increased to 88,888 plants ha-1 was, however, higher for the new hybrids than for the old commercial hybrids. In Tudun Wada, five hybrids produced significantly higher mean grain yields than the remaining hybrid sat both plant densities. One of the hybrids (M1227-12) produced the highest grain yield at both planting densities at this location. In Samaru Zaria, the hybrid M1227-12 produced the highest grain yield only at 53,333 plants ha-1 at this location, whereas M0926-8 produced the highest yield at 88,888 plants ha-1. The 500-grain weight was 7-8% lower at 88,888 plants ha-1 than at 53,333 plantsha-1, which was offset by a significant increase in grain number. Our results showed that farmers in the Nigeria savannas can increase planting density of hybrid maize to 88,888 plants ha-1 and significantly increase their yields.